2007
DOI: 10.1007/s10552-007-9007-7
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine: knowledge and attitudes in two Appalachian Kentucky counties

Abstract: Although a relatively high percentage of women found the HPV vaccination acceptable for their own use, there was less enthusiasm for supporting vaccination to girls. This finding is of concern since the vaccine is being recommended for adolescent girls and young women, prior to sexual initiation. Educational campaigns will be needed for a successful vaccine implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 34 publications
6
48
1
1
Order By: Relevance
“…The present study has shed light on interest among rural Southeast Asian women in receiving the HPV vaccine. The intention to receive the vaccine (65%) is similar to that found in a recent study on rural Southern American women [11]. It is of interest to note that our study was conducted approximately 2 years after the release of the HPV vaccine in our market and before the widespread media coverage.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The present study has shed light on interest among rural Southeast Asian women in receiving the HPV vaccine. The intention to receive the vaccine (65%) is similar to that found in a recent study on rural Southern American women [11]. It is of interest to note that our study was conducted approximately 2 years after the release of the HPV vaccine in our market and before the widespread media coverage.…”
Section: Discussionsupporting
confidence: 70%
“…Numerous studies have demonstrated that public awareness of HPV, perceived risks of HPV infection, and knowledge of potential health consequences of HPV infection are low [8][9][10]. Factors associated with the acceptability of the HPV vaccine are knowledge about the disease, beliefs about vaccines, physician recommendation, previous experience with HPV infections, perceived risk for HPV infection, perceived vaccine safety and efficacy, and perceived vaccination would promote adolescent sexual behavior [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An American study reported that women who were younger and smoker were more likely to receive the HPV vaccine (Hopenhayn et al, 2007). In this study, knowledge about Pap smear test, having knowledge of risk factors for cervical cancer such as having multiple sex partners, sexual intercourse before the age of 18 years, smoking, and having contracted any STDs significantly predicted willingness to accept HPV vaccination.…”
Section: Discussionmentioning
confidence: 67%
“…A review of seven studies found that 58% of respondents had never heard of HPV (12). Awareness was especially low among certain groups, including adolescents, lowerincome individuals, and minorities (16). Moreover, HPV awareness did not ensure accurate knowledge (14), and many did not know that HPV can cause cervical cancer (12,14,17).…”
Section: Introductionmentioning
confidence: 99%